QUALITY PARAMETERS OF SOME NATURAL RUBBER (NR) CLONES INDIGENOUS TO NIGERIA. II. IONIC CONTENT, STABILITY AND DEGRADATION RESISTANCE OF NATURAL RUBBER - Adeosun, B F; Olaofe,; Ajayic, J D (Biological Sciences - PJSIR, 2003)
The degradation resistance. protein content and the ionic analysis of the lattices of two local natural rubber (NR) clones (NNRL-Ilawe Ekiti) and NNRG-lgede Ekiti) and an internation al natural rnbber clone (TJI-Malaysia) have been studied. The international clone (TJ1) was observed to be more resista nt to oxidative degradation than the local clones. The resistance of NR to oxidative breakdown was improved by oxalic and phosphoric acid additives and ,,as fou nd to be related to absolute temperature by an Arrheni us type of equation thereby allowing for the evaluation of the activation energy which is taken to be a measure of the degradation resistance of NR. The lat1ice of the inernational clone ([ fl) appears supe rior to the l at1i ces of the local clon es exa min ed , being of higher protein con tent, stability an d degradation resistance.